PENGEMBANGAN BUKU CERITA SUNAN KALIJAGA BERBAHASA ARAB UNTUK SISWA MI/SD ISLAM DI KABUPATEN DEMAK (Universitas Negeri Semarang, 2022)
Still the lack of availability of Arabic storybooks for students makes students' reading interest less, especially reading Arabic. Many teachers rarely use storybooks in Arabic learning. Therefore researchers developed the Arabic-language Sunan Kalijaga storybook to motivate and develop an interest in reading students' Arabic. This research is a research and development design. The result of this study is that teachers and students want the development of Sunan Kalijaga storybooks in Arabic. The assessment of the validation questionnaire by experts and teachers on the feasibility aspects of the content and material received a score of 3.40. In the aspect of feasibility of presentation (display) get a value of 3.13. In the aspect of language eligibility get a score of 2.99. Meanwhile, in the aspect of graphics feasibility get a value of 3.05.